Partnering between main contractors and sub-contractors in construction projects - Ali, Maisarah; Mohd. Yunus, Yahaya; Shiekhaden, Liban Hassan (2012)
In many construction projects, main contractors usually sublet most of their construction works to domestic sub-contractors especially specialist works in order to lower their overhead costs in terms of employment and equipment costs. The sub-contractors are hired only when their services are needed to undertake the certain works in the project and they are usually hired based on competitive biddings. This is one of the reason identified causing poor relationship between main contractors and domestic sub-contractors. Another problem with such an arrangement is the lack of early involvement of domestic sub-contractors in the construction process. Partnering was identified as one of the solution to this adversarial relationship.The objective of this study is to look at the possibility of partnering between main contractors and sub-contractors and identify benefits from partnering between the two. The results of the study indicate that Malaysia construction business environment is based on competitive bidding, confirming that the Malaysian construction industry is very competitive and business relations are short-termed in nature. The main contractors in Malaysia normally place more emphasis on the consideration of lowest bid price ahead of relationship factors in the selection of domestic sub-contractors although most of them acknowledge the benefit of partnering with their sub-contractors. Keywords: Partnering, main contractor, domestic sub-contractor, competitive bidding